Catalyst system for steam reforming of methanol. - Bösmann, Andreas; Enzenberger, Florian; Maaß, Hans-Jürgen; Wasserscheid, Peter (2012)
A catalyst system for steam reforming of methanol includes a porous catalyst support at the surface of which catalytically active centers are arranged, as well as a salt melt contg. inorg. cations and org. anions which covers at least a part of the surface and the catalytically active centers. The catalyst support can be carbon, titania, alumina, silica, and/or zirconia. The catalytically active centers can consist of Pt, Pd, Ru, Rh, Ir, Cu, and/or Zn. The salt melt can contain Li+, Na+, K+, Cs+, Mg2+, Ca2+, Ba2+, Al3+, Sc3+, and La3+ as cations. The anions of the salt melt can be ions of the general formula R1-COO-, R2-SO3-, R3-O-SO3-, R4-PO4-R5-, and (R6-SO2-)2N- with R1, R2, R3, R4, R5, and R6 being the same or different aliph., alicyclic, or arom. C1-30 hydrocarbon rests the H atoms of which may be substituted by F atoms, hydroxy groups, or carboxylate groups. [on SciFinder(R)]
Keywords: catalyst system steam reforming methanol salt melt porous support

Catalytic production of hydrogen from glucose and other carbohydrates under exceptionally mild reaction conditions - Taccardi, Nicola; Assenbaum, Daniel; Berger, Markus; Bösmann, Andreas; Enzenberger, Florian; Woelfel, Rene; Neuendorf, Stephanie; Göke, Volker; Schödel, Nicole; Maaß, Hans-Jürgen; Kistenmacher, Hans; Wasserscheid, Peter (Green Chemistry, 2010)
A catalytic reaction system for the production of hydrogen from sugars and even water-insoluble biomass like cellulose is presented. The reaction system is based on an ionic liquid that has the role to dissolve the carbohydrate feedstock and a ruthenium catalyst. As hydrogen dissolves in this media at very low level, hydrogen consuming side reactions have been hindered, leading to a gaseous product mixture consisting mainly of hydrogen and carbon dioxide. Investigations with isotopic labelling suggest a reaction sequence in which glucose first thermally decomposes to formic acid followed by Ru-catalyzed decomposition of the latter to hydrogen and CO_2.

Enhanced Activity and Selectivity in Catalytic Methanol Steam Reforming by Basic Alkali Metal Salt Coatings - Kusche, Matthias Manfred; Enzenberger, Florian; Bajus, Stephanie; Niedermeyer, Heiko Jannes; Bösmann, Andreas; Kaftan, Andre; Laurin, Mathias; Libuda, Jörg; Wasserscheid, Peter (Angewandte Chemie International Edition, 2013)
Pt on alumina catalysts can be used for converting methanol and water into hydrogen and carbon dioxide, for applications such as hydrogen storage. Both the activity and selectivity could be enhanced by coating these materials with a thin layer of a molten salt mixture of Li/K/Cs acetate. Potassium doping was indentified by DRIFTS measurements to be an important factor for the boost in catalyst performance.